Laparoscopic Live Donor Nephrectomy: Comparison of Left-sided and Right-sided Approach in Our First 50 Cases - Marcelino, Albertus; Mochtar, Chaidir Arif; Wahyudi, Irfan; Baskoro, Bagus; Rodjani, Arry; Rasyid, Nur (Indonesian Journal of Urology, 2015)
Objectives: To compare the operative results and outcomes between right and left laparoscopic live donor nephrectomy (LLDN). Methods: We retrospectively analyzed the first 50 consecutive LLDN in Indonesia performed between November 2011 and February 2013. Of these patients, 6 underwent right LLDNs and 44 left LLDNs. All patients underwent LLDNs in Cipto Mangunkusumo Hospital. All LLDNs were done by the same surgical teams. Intraoperative, post-operative donor and recipient data results were compared.Results: There were no significant differences of intraoperative, post-operative and recipient data results in both groups.  The first warm ischemic time (mean±SD, 6min 55sec±145sec vs 7min 37sec±177 sec, p>0.05), the second warm ischemic time (41min 35sec ± 7min 45sec vs 48min 36sec ± 8min 41sec, p>0.05), and the operative time (4hour 41min ± 31min vs 4hour 32min ± 49 min, p>0.05) showed similar results in the right and left LLDN, respectively. Active mobilization on 72-hour post-operation was found in 83,3% in the right LLDN compared to 95,5% (p>0.05). There were no delayed graft function and post-operative hemodialysis within one week in the recipients of right LLDN group. Conclusion: Right LLDN has equal operative results and outcomes compared to left LLDN. Right-sided LLDN may be a judicious approach for donors with unfavorable characteristics of the left kidney.